2016
DOI: 10.1111/apa.13304
|View full text |Cite
|
Sign up to set email alerts
|

Somatic assessments of 120 Swedish children taken into care reveal large unmet health and dental care needs

Abstract: Our study revealed a large unmet need for health and dental care interventions among children placed in foster care and residential care and a systematic strategy is required to address those needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 14 publications
(14 reference statements)
4
39
0
3
Order By: Relevance
“…These children had considerably worse rates on all indicators used in the study (treated and untreated dental caries, dental pain, traumatic dental injuries). High rates of dental problems among children and youth entering or residing in OHC have also been reported in a sprinkling of small sample studies, from the USA, Australia, Spain and Sweden (Kling, Vinnerljung, & Hjern, ; Melbye, Chi, Milgrom, Huebner, & Grembowski, ; Nathanson & Tzioumi, ; Olivan, ; Randsalu & Laurell, ; Swire & Kavaler, ). These results are not surprising, in that research has shown that there are strong links between child maltreatment and poor oral health (Cornelius et al, ; Greene, Chisick, & Aaron, ; Kvist, ; Valencia‐Rojas, Lawrence, & Goodman, ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…These children had considerably worse rates on all indicators used in the study (treated and untreated dental caries, dental pain, traumatic dental injuries). High rates of dental problems among children and youth entering or residing in OHC have also been reported in a sprinkling of small sample studies, from the USA, Australia, Spain and Sweden (Kling, Vinnerljung, & Hjern, ; Melbye, Chi, Milgrom, Huebner, & Grembowski, ; Nathanson & Tzioumi, ; Olivan, ; Randsalu & Laurell, ; Swire & Kavaler, ). These results are not surprising, in that research has shown that there are strong links between child maltreatment and poor oral health (Cornelius et al, ; Greene, Chisick, & Aaron, ; Kvist, ; Valencia‐Rojas, Lawrence, & Goodman, ).…”
Section: Introductionmentioning
confidence: 79%
“…In Sweden, approximately 4% of all children are at some time during their childhood placed in societal out‐of‐home care (OHC, foster family or residential care), around the same proportion as in Denmark and the UK (Fallesen, Emanuel, & Wildeman, ; McGrath‐Lone, Dearden, Nasim, Harron, & Gilbert, ; Vinnerljung, ; Vinnerljung, Hjern, Weitoft, Franzén, & Estrada, ). For several decades, studies from various Western countries have reported strikingly high levels of somatic health problems in this group of children (Arora, Kaltner, & Williams, ; Chernoff, Combs‐Orme, Risley‐Curtiss, & Heisler, ; Halfon, Mendonca, & Berkowitz, ; Hansen, Mawjee, Barton, Metcalf, & Joye, ; Kling, Vinnerljung, & Hjern, ; Nathanson & Tzioumi, ; Schor, ; Steele & Buchi, ; Turney & Wildeman, ; Zewdu, ). In addition, adults with childhood experience of OHC have far higher rates of health problems than peers without this background (Vinnerljung, Brännström, & Hjern, ; Schneider et al, ; Viner & Taylor, ; Zlotnick, Tam, & Soman, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, children are defined as individuals under the age of 18 and the out‐of‐home care system includes being cared for by family or friends, being placed with a foster care family, in institutional foster homes or in juvenile detention facilities. Research has shown that approximately 4% of all children in Sweden are placed in out‐of‐home care at some time before the age of 18 years and that these children have poorer physical and mental health than the general population . Case file studies have suggested that health issues are given a low priority by child welfare authorities in Sweden .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, Rauter et al identified numerous unrecognised health needs in 4‐ to 6‐year‐old Tasmanian children, despite them living in out‐of‐home care for an average of three years. However, even in a country like Sweden, which has a free of charge and comprehensive healthcare system, studies have shown that children entering or living in foster care often have significant unmet health needs and are generally less healthy than other children. However, in this integrative literature review, Schneiderman et al compared weight changes in children placed in foster care for one year and found that children who changed weight category showed a trend towards normal weight.…”
Section: Discussionmentioning
confidence: 99%